Integrating maternal depression care at primary private clinics in low-income settings in Pakistan: A secondary analysis - Owais, Syeda Somyyah; Horner, Ronnie D.; Khan, Muhammad Amir; Kenison, Kelli; Probst, Janice C. (Frontiers in Global Women's Health, 2023)
Introduction The prevalence of depression among women in Pakistan ranges from 28% to 66%. There is a lack of structured mental healthcare provision at private primary care clinics in low-income urban settings in Pakistan. This study investigated the effectiveness and processes of a facility-based maternal depression intervention at private primary care clinics in low-income settings. Materials and methods A mixed-methods study was conducted using secondary data from the intervention. Mothers were assessed for depression using the Patient Health Questionnaire-9 (PHQ-9). A total of 1,957 mothers (1,037 and 920 in the intervention and control arms, respectively) were retrieved for outcome measurements after 1 year of being registered. This study estimated the effectiveness of the depression intervention through cluster adjusted differences in the change in PHQ-9 scores between the baseline and the endpoint measurements for the intervention and control arms. Implementation was evaluated through emerging themes and codes from the framework analysis of 18 in-depth interview transcriptions of intervention participants. Results Intervention mothers had a 3.06-point (95% CI: −3.46 to −2.67) reduction in their PHQ-9 score at the endpoint compared with their control counterparts. The process evaluation revealed that the integration of structured depression care was feasible at primary clinics in poor urban settings. It also revealed gaps in the public–private care linkage system and the need to improve referral systems. Conclusions Intervening for depression care at primary care clinics can be effective in reducing maternal depression. Clinic assistants can be trained to identify and deliver key depression counseling messages. The study invites policymakers to seize an opportunity to implement a monitoring mechanism toward standard mental health care.